Determinación de los requerimientos de riego del cultivo de Achira (Canna edulis, Ker Gawier; Canna indica, L) y sus estadios fenológicos, con riego por asperción, en el sector Cabrería - Chumberos, perteneciente al sistema de riego Palmira - Carrillo, José Vicente (2014)
Achira (Canna edulis or Canna indica) is a native crop of the Andean Region that has an enormous potential for the region’s development and expansion. Its principal product is the starch, commonly known as “chuno” that is the result of processing its cormas. This flour is used as an ingredient in popular foods, in the elaboration of canned products, in the pharmaceutical, textile, paper and adhesives industries, and in medicinal uses. Achira as a crop is very important economically to rural families in the southwest sector of Loja canton (Ecuador), specifically in the parishes of Vilcabamba, Quinara, San Pedro de Vilcabamba, Yangana and Malacatos. It can be found in nearly all gardens farmed by Loja’s rural producers. Previous studies of achira have examined botanical and agronomic elements of the plant, while others have looked at the physical, chemical, and organoleptic properties of the starch. However, these studies have failed to investigate the basic water requirements necessary to plant this crop in irrigated areas. The following investigation, “Determination of irrigation requirements to cultivate achira (Canna edulis, Canna indica) and its phenological stages, with aspersion watering in the Cabrería-Chumberos sector, belonging to the Palmira’s watering system,” aims to fill this gap in the literature. The Cabrería-Chumberos sector is located in Quinara parish, Loja canton, Loja province, Ecuador. It has an average yearly temperature of 20°C, receives an average of 773,1 mm of precipitation annually, and is located at an altitude of 1559 meters. Concurrently, the general objective was to determine achira’s hydric requirements through the analysis of the evapotranspiration rate, through references and in the field and to determine the crop coefficient by using aspersion irrigation. This helps make irrigating work more efficient. The specific objectives were: a) determine the phenological phases of achira; b) analyze the evapotranspiration rate through the Penman Monteith procedure and c) estimate the crop coefficient (Kc) of achira by the crop phases defined by the FAO. The variety of achira studied is known as “morada (purple),” so named for the dark vermilion coloration of its leaves (the flower is red). This variety is highly valued by the local farmers, as it is has a higher starch yield than other varieties. Its leaves are also used to wrap local traditional foods. To track phonologic stages, plant specimens were monitored weekly in order to determine the most important physiologic changes in the plant. The reference evapotranspiration (ETo) was calculated daily using a procedure proposed by Penman Monteith: measuring wind speed, insolation, relative humidity and temperature. The information generated by this methodology was compared to the information of a class A evaporimeter; this work included the calibration of a handmade evaporimeter that could be easily installed, managed and interpreted by most farmers. The crop coefficient (Kc) was determined by a FAO methodology based on the relationship between the evapotranspiration rate of the crop in study (ETc) and the evapotranspiration reference. The first one was calculated from the rate of water entering and leaving a drainage lysimeter and the second by means of the procedure mentioned in the previous paragraph. The water requirements of achira were calculated using these parameters. They are based on the difference between the amount of water consumed by the crop and total precipitation during the study period. Information was also obtained from three humidity meters distributed in an experimental block design, with two repetitions. To study the effect of different watering doses on achira yield, all processing was done after harvesting, following the recommendations of expert women from the rural area of La Palmira. Equipment from the communitarian microenterprise “La Achirita” was used. Ten distinct phonological stages were determined according to the BBCH-scale. Using the FAO’s methodology, it was established that the initial stage lasted 57 days, the development stage of the crop 119 days, the half-filled season stage 100 days, and the final season stage 89 days. The total crop cycle was 365 days. The mean values of the crop coefficient obtained in the study were: initial phase 0.66, development phase 0.77, half-filled season phase 0.97; and final phase 0.81. With the completion of the study, the Kc values were established in decadal periods (10 days). With these important parameters, the hydric requirements and subsequent watering needs of achira for the study sector were established. The first method was based on lysimeter data (measuring crop evapotranspiration). The other method used was water provision based on tensiometers readings in the study area. With the help of the lysimeter it was determined that the water required for the crop is 7384.55 m3/ha; discounting rainfall, the total water necessary is 5511.63 m3/ha. However, in the study areas in which the plants were watered every time that the lysimeter reached 20 centibars, the hydric requirements was 7305.57 m3/ha and the watering demand 4907.86 m3/ha, a quantity provided in 16 waterings. In the study areas in which the plants were watered every time the lysimeter reached 30 centibars, the hydric requirement was 6676.36 m3/ha, and the watering demand 4278.65 m3/ha, a volume provided in 15 waterings. In the study areas in which the plants were watered every time that the lysimeter marked 40 centibars, the hydric demand was 6361.75 m3/ha, and the watering demand 3964.04 m3/ha, a volume provided in 13 waterings. The investigation also predicts the influence of different watering doses on starch yield. The projection for one hectare determined that when watered with a tension of 40 centibars, 8412.11 kg/ha (185 quintals/ha) of starch are produced. With tensions of 30 centibars, 8157.03 kg/ha (179.45 quintals/ha) of starch are produced, and with tensions of 20 centibars, 7653.91 kg/ha (168.39 quintals/ha) of starch are produced.